Analysis of Influence of Spindle Speed and Feeding Speed to Tool Wear and Surface Roughness - D.L Zariatin (University of Muhammadiyah Malang, 2016)
One of the problem in metal cutting is tool wear. Its close relation to the expected tool life and quality of product, make tool wear become object of investigation. Eventough tool manufacturers always give recommendation on machining parameter, but they don't share the information on tool wear estimation. Some theory on tool wear has been proposed, but still need verification thru experimental works to determine parameters and constants of tool life typical to machine tool condition and machining process. In this research, experimental work and analysis of the influence of spindle speed (n, rpm), feeding speed (Vf, mm/min) and depth of cut (ap, mm)to surface roughness and tool wear on milling process using carbide ballnose with diameter of 10 mm on Al-7075 had been conducted. From the experiment, it can be concluded that tool wear has influence on surface roughness of product. Tool wear could be minimized by choosing optimum spindle speed and feeding speed.